Improvement of a microfiber filter for domestic washing machines. (1st January 2023) - Masselter, Tom; Schaumann, Uwe; Kampowski, Tim; Ulrich, Kim; Thielen, Marc; Bold, Georg; Speck, Thomas
Abstract: The development of enhanced processes for filtration is one solution for stopping the increasing freshwater and sea pollution caused by microplastic and microfibers. Major contributors to micro-X pollution are domestic devices such as washing machines, which also hold a high technical potential for separating problematic soils from waste water during cleaning cycles. The focus of the present paper are the biomimetic development of a novel concept for filtration and removal of particles such as microfibers in conventional washing machines. To this goal, a TRIZ analysis yielded viable solutions for the major key issues. In a next step, measurements were made with various filters with and without ribbed structures. The results are promising for the incorporation in a filter concept that is easy to operate and cost-effective.